Analisis Kontribusi Guru dalam Menerapkan Keterampilan Kolaborasi Dan Kreativitas Siswa Pada Pembelajaran Sejarah Berbasis Project di MAN 1 Banjarmasin - Yanti, Imbar Desi Mutri; Putro, Herry Porda Nugroho; Sriwati, Sriwati (Prabayaksa: Journal of History Education, 2022)
History learning in the 21st century emphasizes the importance of students having the knowledge and skills that lead to the creation of a smart and competent generation. Presenting history learning that is able to make students the center of learning, actively involved and having skills is a big responsibility for teachers. History teachers must be able to provide variations of learning in the classroom in order to explore students' knowledge and skills to achieve learning objectives. The project-based history learning model is one of the learning strategies that can be chosen by the teacher. Through this learning model, students can act actively and creatively in producing learning products. So the purpose of this research is to analyze the teacher's contribution in applying students' collaboration and creativity skills in project-based history learning. This research was conducted at MAN 1 Banjarmasin. The research method used is a descriptive qualitative approach. Data collection techniques through observation and interviews with history teachers and students of XI IPS 1 MAN 1 Banjarmasin. The results of this study are the use of project-based history learning models can encourage students to have the skills to work together in teams and think creatively in order to produce a product. The teacher's contribution is very important in the implementation of project-based history learning, namely the teacher is involved as a facilitator, mentor, director and assessor. The success of teachers in applying this history learning model can also be seen from the achievement of several indicators of collaboration skills and creativity that students have when working on a given project.